Polycomb protein SCML2 associates with USP7 and counteracts histone H2A ubiquitination in the XY chromatin during male meiosis. - Mengcheng Luo; Jian Zhou; N Adrian Leu; Carla M Abreu; Jianle Wang; Montserrat C Anguera; Dirk G de Rooij; Maria Jasin; P Jeremy Wang (PLoS Genetics)
Polycomb group proteins mediate transcriptional silencing in diverse developmental processes. Sex chromosomes undergo chromosome-wide transcription silencing during male meiosis. Here we report that mouse SCML2 (Sex comb on midleg-like 2), an X chromosome-encoded polycomb protein, is specifically expressed in germ cells, including spermatogonia, spermatocytes, and round spermatids. SCML2 associates with phosphorylated H2AX and localizes to the XY body in spermatocytes. Loss of SCML2 in mice causes defective spermatogenesis, resulting in sharply reduced sperm production. SCML2 interacts with and recruits a deubiquitinase, USP7, to the XY body in spermatocytes. In the absence of SCML2, USP7 fails to accumulate on the XY body, whereas H2A monoubiquitination is dramatically augmented in the XY chromatin. Our results demonstrate that the SCML2/USP7 complex constitutes a novel molecular pathway in modulating the epigenetic state of sex chromosomes during male meiosis.